Strategic Overview of CRPs: Part I. Theories of Change and Impact Pathways - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
The think piece on Theories of Change and Impact pathways, commissioned by the ISPC centers around theoretical articulation of the concept and components of a TOC. It provides a useful assessment of the adequacy and thoroughness by which the CRPs present the assumptions about their research leading to the planned outcomes and impact.